1977
DOI: 10.1084/jem.145.4.892
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of IgE-mediated histamine release from human basophils by viruses: role of interferon.

Abstract: Human leukocytes maintained in culture are induced to release histamine when exposed to ragweed antigen E or anti-IgE. Leukocyte cultures incubated with virus (i.e. HSV-1, Influenza A, and Adeno-1) but not exposed to ragweed antigen E or anti-IgE fail to release histamine. If, however, leukocyte cultures are first exposed to virus and then to ragweed antigen E or anti-IgE, significant enhancement of histamine release occurs. Both infectious and inactivated virus enhance histamine release and the degree of enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
83
2
1

Year Published

1978
1978
1994
1994

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(91 citation statements)
references
References 26 publications
(50 reference statements)
5
83
2
1
Order By: Relevance
“…Recently, Hooks et al (16) have found elevated levels of interferon in the sera of patients with severe systemic lupus erythematosis, and suggested the possibility that this interferon may play a pathogenetic role. Ida and co-workers (17) have suggested that the interferon produced in the course of respiratory infections may be responsible for some of the "allergic" manifestations. If we may extrapolate the results of our study and the extensive studies of De Maeyer et al (9)(10)(11), it seems possible that there is a genetic control for the production of interferon to different viruses in man.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Hooks et al (16) have found elevated levels of interferon in the sera of patients with severe systemic lupus erythematosis, and suggested the possibility that this interferon may play a pathogenetic role. Ida and co-workers (17) have suggested that the interferon produced in the course of respiratory infections may be responsible for some of the "allergic" manifestations. If we may extrapolate the results of our study and the extensive studies of De Maeyer et al (9)(10)(11), it seems possible that there is a genetic control for the production of interferon to different viruses in man.…”
Section: Discussionmentioning
confidence: 99%
“…It seems possible that interferon may also influence other metabolic processes such as energy utilization. In view of these considerations, it is not surprising that interferon can either inhibit or enhance certain cell functions (9)(10)(11)(12)(13)(14)(15)(16)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to interferon's well-known antiviral action, preparations of it have been reported to exert multiple effects on cells [i.e., inhibition of the multiplication of bormal and tumor cells in culture (2)(3)(4)(5), inhibition of the growth of a variety of transplantable tumors in mice (6)(7)(8), modulation of the synthesis and release of specific cellular products (9)(10)(11)(12)(13)(14)(15)(16), modification of the cell surface (17)(18)(19)(20)(21), and modulation of both the humoral (22)(23)(24)(25)(26)(27) and cell-mediated immune responses (28)(29)(30)(31)(32)(33)(34)]. Although experimental results support the hypothesis that the antiviral action of interferon is only one manifestation of its effect on cells (35)(36)(37), it is important to emphasize that these experiments were undertaken using preparations in which interferon protein constituted at most only 1% of the total protein content.…”
mentioning
confidence: 99%
“…Frick et al (1979) determined that viruses could initiate immunological pathways to induce allergic sensitizations to viruses and pollens in children, probably by altering populations of T and B lymphocytes. Additionally, Ida et al (1977) found an enhancement of IgE-mediated histamine release from human basophils by viruses, in conjunction with interferon.…”
mentioning
confidence: 99%